INFLUENCE OF EDUCATIONAL LEVEL ON THE NEUROPHYSIOLOGICAL STATUS OF PATIENTS WITH CORONARY ARTERY DISEASE - Акбиров, Рамиль Мансурович; Тарасова, Ирина Валерьевна; Сырова, Ирина Даниловна (Medicine in Kuzbass, 2018)
Aim – to investigate the parameters of cognitive functions and resting-state EEG power in patients with coronary artery disease (CAD) depending on the educational attainment. Methods. Sixty-six male CAD patients were included in the study. All patients were divided into two groups: the patients with the higher education (about 15 years of learning) and with secondary education (from 8 to 12 years of learning). Neuropsychological examination was performed using the Mini-mental state examination (MMSE) and the Frontal Assessment Battery (FAB). High-resolution monopolar electroencephalography (EEG) was recorded in 64 channels of the 10-20 system in the resting state with eyes closed. Results. It has been established that CAD patients with higher education demonstrate better results of screening neuropsychological scales (MMSE, FAB) compared with CAD patients who have a secondary education (p = 0.004 and p = 0.04, respectively). When comparing the mean values of the spectral power of the resting EEG, it was found that the greater theta rhythms power is characteristic of patients with secondary education compared with persons with higher education (p < 0.05) that indicating a more pronounced dysfunction of the cortex. A correlation analysis between cognitive status indicators and EEG spectral power revealed that higher MMSE scores associated to lower severity of theta activity, while the maximal significance level of the obtained correlations was in the left front-central and parietal regions of both hemispheres of the brain. Conclusions. We concluded that the educational attainment affects not only the cognitive development of the person, but also the severity of signs of cortical dysfunction according to the EEG spectral power in patients with coronary artery disease.